TRANSDISCIPLINARY EXPERIENCES OF ARTISTS AND SCIENTISTS THROUGH THE ILLUSTRATION OF BRAZILIAN MAMMALS - Gonçalves Moura, Juliana; dos Santos Cerqueira Pinto, Dalila; Sawada, Anunciata; Sérgio D’Andrea, Paulo; C. Araujo-Jorge, Tania; Gonçalves-Oliveira, Jonathan (Revista Multidisciplinar de Educação e Meio Ambiente, 2022)
There has been an important dialogue between artists and scientists for many centuries and even today, the creation of environments that favour the interaction of professionals from these two fields provides many potential opportunities for the development of transdisciplinary experiences. In the present study, we describe the experiences of a partnership between the B School and the O Institute, based on the report of a student in art education who, through illustrations of Brazilian mammals, reflects on different aspects of this traits and the potential benefits of this interaction for scientific dissemination, the conservation of species, and the appreciation of art. The experience of the routine of the M laboratory and Mammalogical research, and the rethinking of scientific illustration as an art form, supported novel interpretations of the characteristics of Brazilian mammals and their role in the environment. The illustrations were exhibited at events that promoted public health, scientific dissemination and culture, in both the B School and the O Institute.